Comparison of Medicaid spending in schizoaffective patients treated with once monthly paliperidone palmitate or oral atypical antipsychotics. (2nd April 2016) - Xiao, Yongling; Muser, Erik; Fu, Dong-Jing; Lafeuille, Marie-Hélène; Pilon, Dominic; Emond, Bruno; Wu, Allen; Duh, Mei Sheng; Lefebvre, Patrick
Abstract: Background Compared to oral atypical antipsychotics (OAAs), long-acting injectable antipsychotics require less frequent administration, and thus may improve adherence and reduce risk of relapse in schizoaffective disorder (SAD) patients. Objective To evaluate the impact of once monthly paliperidone palmitate (PP) versus OAAs on healthcare resource utilization, Medicaid spending, and hospital readmission among SAD patients. Methods Using FL, IA, KS, MS, MO, and NJ Medicaid data (January 2009–December 2013), adults with ≥2 SAD diagnoses initiated on PP or OAA (index date) were identified. Baseline characteristics and outcomes were assessed during the 12month pre- and post-index periods, respectively. Propensity score matching (PSM) and inverse probability of treatment weighting (IPTW) were used to reduce confounding and compare the estimated treatment effect for PP versus OAA. Results A total of 10, 778 OAA-treated patients and 876 PP-treated patients were selected. Compared to OAAs, PP was associated with significantly lower medical costs (PSM: mean monthly cost difference [MMCD] = -383, p < 0.001; IPTW: MMCD = -403, p = 0.016), which offset the higher pharmacy costs associated with PP (PSM: MMCD = 270, p < 0.001; IPTW: MMCD = 350, p < 0.001) and resulted in similar total healthcare cost (PSM: MMCD = -113, p = 0.414; IPTW: MMCD = -53, p = 0.697) for PP versus OAA. Reduced risk of hospitalization (PSM: incidence rate ratio [IRR] = 0.85, p = 0.128; IPTW: IRR = 0.96, p = 0.004) and fewer hospitalization days (PSM: IRR = 0.74, p = 0.008; IPTW: IRR = 0.85, p < 0.001) were observed in PP versus OAA patients. Among hospitalized patients, PP was associated with a lower risk of 30 day hospital readmission compared to OAA (IPTW: odds ratio = 0.89, p = 0.041). Limitations The Medicaid data may not be representative of the nation or other states, and includes pre-rebate pharmacy costs (potentially over-estimated). Also changes in treatment over time were possible. Conclusions Total healthcare costs associated with the use of once monthly PP versus OAAs appeared comparable; higher pharmacy costs for PP users were offset by lower medical costs related to fewer and shorter inpatients visits.